2021
DOI: 10.1002/anie.202103427
|View full text |Cite
|
Sign up to set email alerts
|

B–B vs. B–H Bond Activation in a (μ‐Hydrido)diborane(4) Anion upon Cycloaddition with CO2, Isocyanates, or Carbodiimides

Abstract: The intriguing (m-hydrido)diboranes(4) with their prominent pristine representative [B 2 H 5 ] À have mainly been studied theoretically.W en ow describe the behavior of the planarizedt etraaryl (m-hydrido)diborane(4) anion [1H] À in cycloaddition reactions with the homologous series of heterocumulenes CO 2 ,i PrNCO,a nd iPrNCNiPr.W es how that a C = Obond of CO 2 selectively activates the B À Bbond of [1H] À , while the m-H ligand is left untouched( [ 2H] À ). The carbodiimide iPrNCNiPr,i nc ontrast, neglects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 97 publications
3
20
0
Order By: Relevance
“…[ 31 , 47a ] To test this proposal, we treated 4 with 1 equiv of Li[ 2 H], which here served as a storage form of [ 8 ] − (Scheme 6 ). [ 23 , 32 , 33 ] Indeed, Li[ 5 ] and the byproduct 1 ⋅thf were obtained in equimolar amounts and with perfect selectivity. [56]
Scheme 6 Reaction of Li[ 2 H] with 4 in THF gives Li[ 5 ] and 1 ⋅thf, likely via the Li[ 8 ]⋅ 1 adduct, which liberates a borafluorenyl anion [ 8 ] − (green) for insertion into one B−C bond of 4 (blue; carbon atoms marked with asterisks bear t Bu substituents).
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 31 , 47a ] To test this proposal, we treated 4 with 1 equiv of Li[ 2 H], which here served as a storage form of [ 8 ] − (Scheme 6 ). [ 23 , 32 , 33 ] Indeed, Li[ 5 ] and the byproduct 1 ⋅thf were obtained in equimolar amounts and with perfect selectivity. [56]
Scheme 6 Reaction of Li[ 2 H] with 4 in THF gives Li[ 5 ] and 1 ⋅thf, likely via the Li[ 8 ]⋅ 1 adduct, which liberates a borafluorenyl anion [ 8 ] − (green) for insertion into one B−C bond of 4 (blue; carbon atoms marked with asterisks bear t Bu substituents).
…”
Section: Resultsmentioning
confidence: 99%
“…[ 31 , 47a ] To test this proposal, we treated 4 with 1 equiv of Li[ 2 H], which here served as a storage form of [ 8 ] − (Scheme 6 ). [ 23 , 32 , 33 ] Indeed, Li[ 5 ] and the byproduct 1 ⋅thf were obtained in equimolar amounts and with perfect selectivity. [56]…”
Section: Resultsmentioning
confidence: 99%
“…The resulting intermediate Na[ 10 ] can be regarded as adduct between a Lewis basic 9‐borafluorenyl anion [ 8 ] − and a Lewis acidic 9‐butyl‐9‐borafluorene (compare the related adduct Li[ 8 ]⋅ 1 in Scheme 6). In a follow‐up step, [ 8 ] − inserts into the C α −H bond of the n ‐butyl chain to form Na[ 9 ] [30, 32, 33] . The vigorous reactivity of Na 2 [ 3 ] also became apparent when we tried to record cyclic voltammograms of the compound, since the initial blue‐green color of the THF solution quickly faded on contact with the supporting electrolyte [ n Bu 4 N][PF 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24] In the recent past, we have investigated in detail the alkali-metal reduction of the 9H-9-borafluorene dimer (1) 2 or of the THF adduct 1•thf (Scheme 2). [25][26][27][28][29][30][31][32][33][34] Specifically,w e found that treatment of 1•thf with an excess of Li granules in THF leads to ap roduct mixture from which Li 2 [2], ad oubly boron-doped analogue of dibenzo[g,p]chrysene (C), could be isolated in approximately 45 %yield (Scheme 2). [35] Asecond major product is the borafluorene-dianion salt Li 2 [1](approx.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation